Project management for business professionals : a comprehensive guide - Knutson, Joan (John Wiley, 2001)
No longer restricted to the engineering industry, project management has at long last crossed over to mainstream business. Project Management for Business Professionals is the definitive reference on the essentials of contemporary project management. Featured here are some of the foremost practitioners and researchers from academia, consulting, and private industry, sharing their various areas of project management expertise and providing a wide range of perspectives on everything from risk management to resource planning to ethics management.